2007
DOI: 10.1002/prot.21412
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of exchanging domains between LacI and PurR are mediated by the intervening linker sequence

Abstract: Homologue function can be differentiated by changing residues that affect binding sites or long-range interactions. LacI and PurR are two proteins that represent the LacI/GalR family (>500 members) of bacterial transcription regulators. All members have distinct DNA-binding and regulatory domains linked by approximately 18 amino acids. Each homologue has specificity for different DNA and regulatory effector ligands; LacI and PurR also exhibit differences in allosteric communication between DNA and effector bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(129 citation statements)
references
References 79 publications
5
124
0
Order By: Relevance
“…For example, LLhP (a chimera with the LacI DNA-binding domain and linker and the PurR regulatory domain), is co-repressed; whereas the LLhG chimera with the GalR regulatory domain is induced, each by their respective ligands 19; 21. In this study, we expected and observed similar effector responses for LPhP and LGhG chimeras.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…For example, LLhP (a chimera with the LacI DNA-binding domain and linker and the PurR regulatory domain), is co-repressed; whereas the LLhG chimera with the GalR regulatory domain is induced, each by their respective ligands 19; 21. In this study, we expected and observed similar effector responses for LPhP and LGhG chimeras.…”
Section: Resultssupporting
confidence: 60%
“…LPhP and LGhG were constructed in order to compare the functional contributions of PurR and GalR linker positions to those in the LacI linkers in LLhP and LLhG19; 21. In Materials and Methods, we present our criteria for designing the chimeric repressors and for interpreting in vivo repression resultsb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a model is consistent with mutagenesis of an engineered homologue, which showed that linker interface mutations can alter repression of either or both the low-and high-affinity complexes. 56 The ternary oDNA complex must occur in vivo, but is short-lived, since excess genomic DNA effectively competes to displace the repressor protein from the operator. [16][17][18] Therefore, another question is whether the structure of LacI in the oDNA ternary complex is distinct from the repressor structure in complex with nDNA.…”
Section: Discussionmentioning
confidence: 99%
“…In mathematical terms, this implies an additive effect of o and r over the mutation rates, c, i 1 , j 2 , and k 2 , (Table S1, ESI †). This intrinsic TF interaction has been experimentally reported, at least for the well-documented LacI, by molecular structure analysis, 15 and by changing residues that affect the binding site, 16 among others.…”
Section: Model Assumptionsmentioning
confidence: 90%